Population Genetic Structure and Selection Signature Analysis of Beijing Black Pig - Yang, Wenjing; Liu, Zhen; Zhao, Qiqi; Du, Heng; Yu, Jian; Wang, Hongwei; Liu, Xiance; Liu, Hai; Jing, Xitao; Yang, Hongping; Shi, Guohua; Zhou, Lei; et al. (Frontiers in Genetics, 2022)
Beijing Black pig is an excellent cultivated black pig breed in China, with desirable body shape, tender meat quality and robust disease resistance. To explore the level of admixture and selection signatures of Beijing Black pigs, a total number of 90 individuals covering nine pig breeds were used in our study, including Beijing Black pig, Large White, Landrace, Duroc, Lantang pig, Luchuan pig, Mashen pig, Huainan pig and Min pig. These animals were resequenced with 18.19 folds mapped read depth on average. Generally, we found that Beijing Black pig was genetically closer to commercial pig breeds by population genetic structure and genetic diversity analysis, and was also affected by Chinese domestic breeds Huainan pig and Min pig. These results are consistent with the cross-breeding history of Beijing Black pig. Selection signal detections were performed on three pig breeds, Beijing Black pig, Duroc and Large White, using three complementary methods (FST, θπ, and XP-EHH). In total, 1,167 significant selected regions and 392 candidate genes were identified. Functional annotations were enriched to pathways related to immune processes and meat and lipid metabolism. Finally, potential candidate genes, influencing meat quality (GPHA2, EHD1, HNF1A, C12orf43, GLTP, TRPV4, MVK, and MMAB), reproduction (PPP2R5B and MAP9), and disease resistance (OASL, ANKRD13A, and GIT2), were further detected by gene annotation analysis. Our results advanced the understanding of the genetic mechanism behind artificial selection of Beijing Black pigs, and provided theoretical basis for the subsequent breeding and genetic research of this breed.